2014
DOI: 10.1002/bjs.9709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymph node ratio on survival in patients with pancreatic and periampullary cancer

Abstract: LNR is a common predictor of poor survival in pancreatic, distal CBD and ampullary cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 48 publications
7
78
1
Order By: Relevance
“…Sensitivity analysis was performed for PDAC separately, as outcomes may differ from periampullary (distal CBD, papilla, duodenum) cancers, and clear differences exist in survival between the various periampullary cancers and PDAC. 35,36 Therefore, some of the largest studies in this review describing only 'cancer of the pancreatic head' which may involve distal cholangiocarcinoma were excluded from sensitivity analysis. Survival in patients with PDAC and LNM was shorter compared to patients with other periampullary cancers and LNM: survival in patients with PDAC and hepatic-artery or para-aortic LNM was 13 and 11 months, respectively, compared to 15 and 13 months for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analysis was performed for PDAC separately, as outcomes may differ from periampullary (distal CBD, papilla, duodenum) cancers, and clear differences exist in survival between the various periampullary cancers and PDAC. 35,36 Therefore, some of the largest studies in this review describing only 'cancer of the pancreatic head' which may involve distal cholangiocarcinoma were excluded from sensitivity analysis. Survival in patients with PDAC and LNM was shorter compared to patients with other periampullary cancers and LNM: survival in patients with PDAC and hepatic-artery or para-aortic LNM was 13 and 11 months, respectively, compared to 15 and 13 months for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph-nodes status is one of the most powerful predictors of survival after resection in patients with periampullary cancer [34] . By performing a more detailed analysis, we have shown that the median survival was impaired in stented patients independent of lymph-node status.…”
Section: Discussionmentioning
confidence: 99%
“…The relative prognostic value of each of these lymph node-/lymphatic vasculature-specific metrics is controversial. Prospective and retrospective clinical studies evaluating the utility of these criteria are collected in Table 2 [6,33,38,44,51,62,63,101ā€“104,106ā€“114]. Contradictory conclusions from these studies highlight the remaining need for additional work before use of these metrics is informative in the general clinical setting.…”
Section: Outcomes Prediction: Lymphatic-specific Metricsmentioning
confidence: 99%